Die Vermögensverteilung in Österreich und das Aufkommenspotenzial einer Vermögenssteuer - Eckerstorfer, Paul; Halak, Johannes; Kapeller, Jakob; Schütz, Bernhard; Springholz, Florian; Wildauer, Rafael (Wirtschaft und Gesellschaft, 2014)
This paper estimates the potential revenues of a wealth tax for Austria. This becomes possible due to the first comprehensive survey on Austrian household wealth (Household Finance and Consumption Survey, HFCS), which was coordinated by the European Central Bank and conducted by the Austrian National Bank. Surveys concerning sensitive data such as personal wealth do, however, face the problem that they do not accurately capture the top of the distribution, i.e. the wealthiest households. Since a considerable amount of wealth is concentrated in the hands of very few households, this leads to an underestimation of total wealth as well as biased results concerning the distribution of wealth. In order to compensate for this shortcoming, we employ the common assumption that the wealthiest households can be described by a Pareto distribution. Here we first specify a proper Pareto distribution according to statistical criteria and then use this Pareto distribution to correct the upper part of the wealth distribution. Due to this correction, total private wealth increases from about 1,000 billion Euros to 1,249 billion Euros, where the correction has the largest impact for the richest 1% of households. The wealth of the latter increases by 98.6%, i.e. from 6.4 billion.Euros to 12.7 billion Euros. The potential revenue of a wealth tax depends on the applied tax model as well as the assumed behavioural responses. The impact of the data correction is most apparent for progressive tax models.